2016
DOI: 10.1039/c6ra14010f
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and optical property of metal-doped Ga2O3: a first principles study

Abstract: A long list of main group and transition metals, even some lanthanides, have been examined based on first principles studies, to search for potential p-type dopants for β-Ga2O3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 55 publications
8
52
0
Order By: Relevance
“…2 On the other hand, the CB is formed by In-5s, Ga-4s, Zn-4s and O-2s orbitals along with the O-2p orbitals. Interestingly, a contribution of Ga-3d and In-4d states in the higher VB region is observed, and a similar d-state character has been reported for Ga2O3 and In2O3 [27,28]. To clarify the presence of the high-lying d-states, additional calculations are performed for Ga2O3 as an example.…”
Section: Electronic and Optical Propertiessupporting
confidence: 66%
“…2 On the other hand, the CB is formed by In-5s, Ga-4s, Zn-4s and O-2s orbitals along with the O-2p orbitals. Interestingly, a contribution of Ga-3d and In-4d states in the higher VB region is observed, and a similar d-state character has been reported for Ga2O3 and In2O3 [27,28]. To clarify the presence of the high-lying d-states, additional calculations are performed for Ga2O3 as an example.…”
Section: Electronic and Optical Propertiessupporting
confidence: 66%
“…β -Ga 2 O 3 exhibits complex optoelectronic behavior as a result of its low-symmetry crystal structure, coincidences of energy levels, self-trapped polaron, and excitonic effects 57 . Three important features have been reported in the literature: ( i ) its optical properties are highly anisotropic, ( ii ) the minimum direct optical transition is symmetry-forbidden at its lowest energy, and ( iii ) its emission spectrum does not typically exhibit near-band-edge emission 8 .…”
Section: Introductionmentioning
confidence: 99%
“…SIMS measurements have shown that only samples grown by the maximum flux 3.8 µmol had detectable level of Zn atoms. Estimated concentrations for both substrates are very similar: [Zn] = 1.5×10 19 at/cm -3 for Ga2O3 on sapphire (0001) and [Zn] = 3.2×10 19 at/cm -3 for Ga2O3 on Si (111), which is about 0.5% of doping level. This value agrees very well with the value extracted from energy-dispersive X-ray spectroscopy (EDX) profile from a transmission electron microscopy (TEM) measurements performed on the Zn:Ga2O3/Si sample..…”
Section: Structural Propertiesmentioning
confidence: 83%
“…However, for C. Zhang and coauthors, an atomic Zn concentration of ~ 4% has been estimated to introduce shallow levels above the valence band at around 0.3 eV [17]. Contrary to this statement, for ~1.5% doping, Zn has been reported to be a very deep acceptor with > 1.2 eV energy level above valence band maximum [18] with low activation rate [19]. Co-doping Zn-N has been reported as well, and refereeing an acceptor with possibly 0.5 eV activation energy [20].…”
Section: Intrinsic and Zn-doped P-type Ga2o3 A Reviewmentioning
confidence: 91%